A Cross-Country Analysis of Islamic Bank’s Performance in Malaysia and Indonesia - Moh. Nurul Qomar; Sulistya Rusgianto; Ibnu Muttaqin; Athi’ Hidayati (Universitas Muhammadiyah Malang, 2024)
This study aims to examine the financial performance of Islamic banks in Indonesia and Malaysia, with a specific focus on optimizing shareholder value. The assessment includes efficiency, market share, interest rates, inflation and economic growth as crucial criteria in comprehending the success of Islamic banks in each country. The secondary data is derived from the annual reports of 25 Islamic banks in Indonesia and Malaysia, with a focus on characteristics pertaining to operational efficiency and market share. Furthermore, data is obtained from Bank Indonesia (BI) to gather statistics regarding inflation, interest rates, and GDP growth from the years 2018 to 2021. The study used panel data regression with a random effects model as the most accurate estimator. The results of the panel data regression analysis suggest that inflation has a favorable effect on return on equity (ROE), while GDP growth has a beneficial impact on return on assets (ROA). This research highlights the importance of enhancing inflation risk management and making strategic adaptations to the business plans of Islamic banks in Malaysia and Indonesia. This research enhances the scholarly comprehension of the variables affecting the efficiency of Islamic banks in diverse economic conditions.